Collective responsibility and accountability under international law - Darcy, Shane (Procedural aspects of international law series ;, 2007)
"Accountability in International Law" examines the extent to which the basic principle of individual responsibility accommodates liability for the acts of others. It examines the debates and legal developments surrounding collective responsibility under international law. The philosophical debates on collective responsibility provide an introduction to the examination of whether collective responsibility is ever appropriate or even lawful under international law. As the international criminal justice project begins to flourish, it is of paramount importance that the extent of the pot.